Valve-Like Outflow System Behavior With Motion Slowing in Glaucoma Eyes: Findings Using a Minimally Invasive Glaucoma Surgery–MIGS-Like Platform and Optical Coherence Tomography Imaging - Johnstone, Murray; Xin, Chen; Acott, Ted; Vranka, Janice; Wen, Joanne; Martin, Elizabeth; Wang, Ruikang K. (Frontiers in Medicine, 2022)
Purpose This study aimed to investigate anatomic relationships and biomechanics of pressure-dependent trabecular meshwork and distal valve-like structure deformation in normal and glaucoma eyes using high-resolution optical coherence tomography (HR-OCT). Methods We controlled Schlemm’s canal (SC) pressure during imaging with HR-OCT in segments of three normal (NL) and five glaucomatous (GL) ex vivo eyes. The dissected limbal wedges were studied from 15 locations (5 NL and 10 GL). A minimally invasive glaucoma surgery (MIGS)-like cannula was inserted into the SC lumen, whereas the other end was attached to a switch between two reservoirs, one at 0, the other at 30 mm Hg. A steady-state pressure of 30 mm Hg was maintained to dilate SC and collector channels (CC) during 3D volume imaging. The resulting 3D lumen surface relationships were correlated with internal structural features using an image mask that excluded tissues surrounding SC and CC. While imaging with HR-OCT, real-time motion responses in SC and CC areas were captured by switching pressure from 0 to 30 or 30 to 0 mm Hg. NL vs. GL motion differences were compared. Results Lumen surface and internal relationships were successfully imaged. We identified SC inlet and outlet valve-like structures. In NL and GL, the mean SC areas measured at the steady-state of 0 and 30 mm Hg were each significantly different (p < 0.0001). Synchronous changes in SC and CC lumen areas occurred in <200 ms. Measured SC area differences at the steady-state 0 and 30 mmHg, respectively, were larger in NL than GL eyes (p < 0.0001). The SC motion curves rose significantly more slowly in GL than NL (p < 0.001). Pressure waves traveled from the cannula end along the SC lumen to CC and deep intrascleral channels. Conclusion HR-OCT provided simultaneous measurements of outflow pathway lumen surfaces, internal structures, and biomechanics of real-time pressure-dependent dimension changes. We identified SC inlet and outlet valve-like structures. GL tissues underwent less motion and responded more slowly than NL, consistent with increased tissue stiffness. A MIGS-like shunt to SC permitted pulse waves to travel distally along SC lumen and into CC.